Calculation Technique of Dynamic Electro-Pneumatic Drive Characteristics of Manipulator Hand - F. K. Cravec; R. R. Levko (Наука и техника)
The paper contains a calculation scheme, a mathematical model and calculation technique of dynamic electro-pneumatic drive of a manipulator hand with due account of microprocessor control. The results of calculation of dynamic electro-pneumatic drive characteristics are given in the paper. The given technique can be used while developing perspective electro-pneumatic systems of technological and mobile machines.